Last updated at May 29, 2018 by Teachoo

Transcript

Misc 1 Show that the sum of (m + n)th and (m – n)th terms of an A.P. is equal to twice the mth term. First we calculate (m + n)th , (m – n)th and mth terms of an A.P We know that an = a + (n – 1)d Where an is nth term of AP a be the first term & d be the common difference of the A.P. For (m + n)th term putting n = m + n in (1) am + n = a + (m + n – 1)d For (m – n)th term putting n = m – n in (1) am – n = a + (m – n – 1)d for mth term putting n = m in (1) am = a + (m – 1)d We need to prove Sum of (m + n)th term & (m – n)th terms is twice of mth term i.e. am + n + am – n = 2am Taking L.H.S am + n + am – n = a + (m + n – 1)d +[a + (m – n – 1)d] = a + a + (m + n – 1)d + (m – n – 1)d] = 2a + (m + n – 1 + m – n – 1 )d = 2a + (m + m – 1 – 1 + n – n)d = 2a + (2m – 2 – 0)d = 2a + 2(m – 1)d = 2[a + (m – 1)d] = 2am = R.H.S Hence L.H.S = R.H.S Hence proved

Miscellaneous

Misc 1
You are here

Misc 2

Misc 3 Important

Misc 4

Misc 5

Misc 6 Important

Misc 7 Important

Misc 8

Misc 9

Misc 10 Important

Misc 11

Misc 12

Misc 13

Misc 14 Important

Misc 15

Misc 16 Important

Misc 17

Misc 18

Misc 19 Important

Misc 20

Misc 21 (i) Important

Misc 21 (ii)

Misc 22 Important

Misc 23 Important

Misc 24 Deleted for CBSE Board 2022 Exams

Misc 25 Important Deleted for CBSE Board 2022 Exams

Misc 26 Deleted for CBSE Board 2022 Exams

Misc 27

Misc 28 Important

Misc 29 Important

Misc 30

Misc 31 Important

Misc 32 Important

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 10 years. He provides courses for Maths and Science at Teachoo.